View of the Neumarkt in Vienna - Delsenbach, Johann Adam, 1687-1765 (engraver):::Creator::::::::::::; Fischer von Erlach, Joseph Emanuel, 1613-1742 (artist):::Contributor:::::::::::: (Austria; Vienna)
Engraving of the Neuer Markt in Vienna from the early eighteenth century, showing a winter parade through the square.